Pengaruh Latihan Menggunakan Media Alat Bantu Robopong dan Spongewheel Terhadap Ketepatan Hasil Pukulan Backhand Spin pada Cabang Olahraga Tenis Meja: PENGARUH LATIHAN MENGGUNAKAN MEDIA ALAT BANTU ROBOPONG DAN SPONGEWHEEL TERHADAP KETEPATAN HASIL PUKULAN BACKHAND SPIN PADA CABANG OLAHRAGA TENIS MEJA - Mardi, Mardi; Muhtar, Tatang; Safari, Indra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of training using robopong and spongewheel media on the accuracy of backhand spin strokes in table tennis. The research method used is experimental, using the Matching-Only Pretest-Posttest Control Group Design design. The population in this study consists of students who are members of the Table Tennis Student Activity Unit (UKM) and comprises 30 samples aged 18-25 years. Sampling was conducted using a purposive sampling technique. The treatment for both the experimental and control groups was performed twice a week over 16 sessions. The final results of the treatment show that both exercises positively affect the improvement of backhand spin shot accuracy in table tennis. In conclusion, based on the average values of both groups, training using the Robopong aid is significantly more influential than training using the Spongewheel aid in improving the accuracy of backhand spin strokes in table tennis. Keywords: Backhand Spin, Media Tools, Robopong, Sponge wheel, Precision,